Multibeam RF Antenna Performance for Indoor Coverage in Stadium - Suzi Seroja Sarnin; Mohd Yusdee Yusoff; Mohamad Yazid Mohamad; Nani Fadzlin Naim; Norsuzila Yaacob (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
The objective of the proposal is to address the demand on data over the services provided by telecommunication industries during major events held in Malaysia especially in stadiums. Previously, during most of the events, users will experience bad services in both data and voice transactions. It is not only slow or delayed but almost failed to access the network to connect them to the world. Besides a few solutions that have been introduced such as IBC (In-Building Coverage) and Small Cells, this proposed solution Multibeam RF Antenna, is one of them to address the demand. This solution has been chosen as it is fast in deployment, easy to maintain and cost effective even if it may not cover the whole targeted areas.This paper will provide analysis, evaluation and actual Walk Test (WT) to show the effectiveness of the Multibeam RF Antenna